Increased Cardiovascular Mortality in Ecuador during COVID-19 Pandemic - Marco Fornasini; Ivan Sisa; Manuel E. Baldeon (Ubiquity Press, 2023)
Before the COVID-19 pandemic, chronic noncommunicable diseases (NCDs), represented a high burden for low and middle-income countries. Patients with NCDs are at higher risk of COVID-19 and suffer worse clinical outcomes. We present mortality trends for myocardial infarction (AMI), stroke, hypertension (HT), and type-2 diabetes mellitus (T2DM) from 2005 to 2021 in Ecuador. The greatest increase in mortality observed in the pandemic was in AMI, T2DM, and HT. Factors related to COVID-19, health services, and patients with NCDs could contribute to these important increases in mortality.